1989
DOI: 10.1159/000125131
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Synapses within the Paraventricular Nucleus of the Hypothalamus

Abstract: Corticotropin-releasing factor (CRF) regulates the release of adrenocorticotropin (ACTH) from the anterior pituitary and these neurosecretory neurons reside in the paraventricular nucleus of the hypothalamus (PVN). In addition to its role as an ACTH secretogogue, exogenously administered CRF can act centrally to modify sympathetic outflow, alter various stress-induced behaviors and modulate its own secretion. Some of these effects might be mediated by CRF acting synaptically within the PVN as the nucleus is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 15 publications
4
35
0
1
Order By: Relevance
“…47 There are also CRF synapses on CRF neurons present in the rat PVN. 48 In our study, the increase of CRF was accompanied by an increase of CRFR1 expression in the PVN. This suggests a Abbreviations: AR, androgen receptor; AVP, vasopressin; AVPR1A, AVP receptor 1a; CRF, corticotropin-releasing factor; CRFR, CRF receptors; CREB, cAMP-response element-binding protein; ESR, estrogen receptor; GR, glucocorticoid receptor; HSP, heat shock protein; IL1b, interleukin 1-b; MR, mineralocorticoid receptor; OXT, oxytocin; PVN, paraventricular nucleus; SON, supraoptic nucleus; TNFa, tumor necrosis factor-a.…”
Section: Crf Neurons and Crfr1 And Crfr2 Imbalancesupporting
confidence: 58%
“…47 There are also CRF synapses on CRF neurons present in the rat PVN. 48 In our study, the increase of CRF was accompanied by an increase of CRFR1 expression in the PVN. This suggests a Abbreviations: AR, androgen receptor; AVP, vasopressin; AVPR1A, AVP receptor 1a; CRF, corticotropin-releasing factor; CRFR, CRF receptors; CREB, cAMP-response element-binding protein; ESR, estrogen receptor; GR, glucocorticoid receptor; HSP, heat shock protein; IL1b, interleukin 1-b; MR, mineralocorticoid receptor; OXT, oxytocin; PVN, paraventricular nucleus; SON, supraoptic nucleus; TNFa, tumor necrosis factor-a.…”
Section: Crf Neurons and Crfr1 And Crfr2 Imbalancesupporting
confidence: 58%
“…Additionally, glutamate (Glu) expressed in these anterior BST nuclei may also stimulate the HPA axis (Forray and Gysling, 2004). Thus, CRHexpressing central amygdalar neurons (Champagne et al, 1998) may activate the HPA axis by connecting with the dorsomedial/ fusiform BST nuclei (Prewitt and Herman, 1998) that express CRH/Glu to form an excitatory, bisynaptic CRH-CRH/Glu signal to the PVNmp (Paull and Gibbs, 1983;Silverman et al, 1989). Alternatively, the central nucleus of the amygdala may stimulate HPA activation (Van de Kar et al, 1991;Buller and Day, 2002) via GABA-GABA transsynaptic disinhibition (Cullinan et al, 1993) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The main output neurons of the amygdala have been demonstrated to contain CRH peptide [35] . There are also synapses on CRH neurons in the rat PVN [36] . The above evidence combined with our findings suggests that the direct CRH neuron-involving connection between PVN and CeA plays an important role in the stress response.…”
mentioning
confidence: 99%
“…Consequently, it regulates the activation of the HPA-axis via projections to the hypothalamus, which might underlie the increase of depressive behaviors and mood alterations. Some reports have indicated that neurons in CeA have direct projections to many areas in brain, including PVN in the hypothalamus [34][35][36][37] . Transmitter release from the amygdala onto PVN has been identified by Gray [35] .…”
mentioning
confidence: 99%